Beruf, Dasein y Ethik Un análisis de los textos de la polémica sobre La ética protestante y el espíritu del capitalismo de Max Weber - Villacañas Berlanga, José Luis (Logos. Anales del Seminario de Metafísica, 2011)
The Protestant Ethic and the Spirit of Capitalism is a well-known book in Spain, but it caused a complex debate that hasn’t been translated or taken into account by the critics. Outside Spain, it hasn’t been used massively for the interpretation of Weber’s thesis either. My essay aims to value all criticisms and anti-criticisms that forced Weber to a refinement of the philosophical dimension of his thesis on the relationship between rationality - irrationality and the metaphysical basis of the latter.